2010
DOI: 10.1590/s0102-09352010000600025
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da granulometria do milho no desempenho de juvenis de pacu, Piaractus mesopotamicus (Holmberg, 1887)

Abstract: RESUMOAvaliou-se o efeito de diferentes granulometrias do milho da ração no desempenho de juvenis de pacu, Piaractus mesopotamicus. Foram utilizados 120 juvenis com peso inicial de 8,42±0,89, comprimento total de 7,03±0,20cm, comprimento padrão de 6,32±0,13cm e altura de 3,21±0,11cm, distribuídos em 20 aquários (300L), na densidade de seis peixes por unidade experimental (aquário), em delineamento inteiramente ao acaso, com cinco tratamentos constituídos por diferentes granulometrias -850, 710, 500, 300, 150μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…Except for orthophosphate values, all the water quality parameters were similar to those reported in previous studies of red tilapia culture (Al-Hafedh et al 2008;Wang et al 2016) and pacu (Polese et al 2010;Fiod et al 2010). Although with higher values compared to other published work, orthophosphate tended to stabilize at the end of the trial (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Except for orthophosphate values, all the water quality parameters were similar to those reported in previous studies of red tilapia culture (Al-Hafedh et al 2008;Wang et al 2016) and pacu (Polese et al 2010;Fiod et al 2010). Although with higher values compared to other published work, orthophosphate tended to stabilize at the end of the trial (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding pacu growth performance, Signor et al (2010) and Polese et al (2010) evaluated different diets for pacu in cages and RAS, respectively and reached mean FCR's of 3.0 and 1.5 and SGR of 0.7 and 1.1% day −1 , respectively. The mean values of FCR obtained by Polese et al (2010) corroborates with our study, but those found by Signor et al (2010) and both SGR values were lower than the 2.35% day −1 reached in our study. These results could indicate a good adaptation of pacu to the aquaponics system.…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro (2007) encontrou efeito linear positivo na taxa de crescimento específico de juvenis de acará-bandeira com o aumento do teor de proteína bruta, e o melhor resultado foi de 1,6% para os animais alimentados com 32,0% de proteína bruta. Polese et al (2010) As diferenças encontradas no desenvolvimento com o aumento da densidade de estocagem podem ser explicadas pelo aumento da competição e pelo estabelecimento de hierarquia na alimentação entre os peixes. Segundo Vera Cruz e Mair (1994), indivíduos dominantes dentro de uma população podem consumir mais alimento e crescer mais rapidamente, deixando menos alimento para os indivíduos submissos, que apresentam menor crescimento.…”
Section: Resultsunclassified
“…Carnivorous fish have high lipase and protease levels (Furné et al, 2005), which benefit the digestibility of animal protein ingredients, while production of enzymes is influenced by factors such as environmental changes (Moura et al, 2007) and dietary particle size (Polese et al, 2010). That explains why the best ADCDM were found for the poultry by-product meal and fish meal.…”
Section: Discussionmentioning
confidence: 99%